2021
DOI: 10.1111/1462-2920.15765
|View full text |Cite
|
Sign up to set email alerts
|

The current situation and potential effects of climate change on the microbial load of marine bivalves of the Greek coastlines: an integrative review

Abstract: Global warming affects the aquatic ecosystems, accelerating pathogenic microorganisms' and toxic microalgae's growth and spread in marine habitats, and in bivalve molluscs. New parasite invasions are directly linked to oceanic warming. Consumption of pathogen-infected molluscs impacts human health at different rates, depending, inter alia, on the bacteria taxa. It is therefore necessary to monitor microbiological and chemical contamination of food. Many global cases of poisoning from bivalve consumption can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 146 publications
(205 reference statements)
1
17
0
Order By: Relevance
“…In particular, with very few exceptions, the major microbial load within marine bivalves in Greece consists of host pathogenic bacteria, protozoans or other parasites, and a far lesser extent of public health harmful microorganisms. Hence, despite the microbial load detected that is in line with a recently published review paper [137], our data suggest that Greek bivalves are microbiologically safe for raw consumption, and the sector of marine bivalve farming and fisheries, when proper depuration takes place in combination with systematic surveillance, shall continue to constitute a considerable primary sector. In this context, the findings of the present study are expected to contribute to defining the safety status of seafood products, in terms of microbial load, in the second largest city in Greece.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In particular, with very few exceptions, the major microbial load within marine bivalves in Greece consists of host pathogenic bacteria, protozoans or other parasites, and a far lesser extent of public health harmful microorganisms. Hence, despite the microbial load detected that is in line with a recently published review paper [137], our data suggest that Greek bivalves are microbiologically safe for raw consumption, and the sector of marine bivalve farming and fisheries, when proper depuration takes place in combination with systematic surveillance, shall continue to constitute a considerable primary sector. In this context, the findings of the present study are expected to contribute to defining the safety status of seafood products, in terms of microbial load, in the second largest city in Greece.…”
Section: Discussionsupporting
confidence: 71%
“…M. refringens is a protozoan parasite of the phylum cercozoan and order Paramyxida causing infection of the digestive gland of the marine bivalves and downregulation of the physiological processes, resulting lower growth rates and even losses in farms and in natural beds [20,133,134]. Detection rates of this parasite are higher in summer months, where temperatures demonstrate higher values in comparison with the winter months, and this phenomenon is amplified due to global climate warming [135][136][137]. Nevertheless, the Aber disease is not yet fully understood [136].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, bivalve farming represents an important marine aquaculture activity worldwide, raising production from nearly 1 million tons in 1950 to 14.54 million tons in 2013, with an annual value of more than USD 15 billion [ 4 , 5 ]. In Greece, although oyster and clam farming have been recently licensed, bivalve cultivation is still represented exclusively by the Mediterranean mussel Mytilus galloprovincialis (Lamarck, 1819) farming [ 6 , 7 , 8 ]. Mussel culture is depending on wild stocks since in the process of mussel farming, spat (juveniles) is collected from collector ropes or traps and transferred to neighboring mussel farming areas for cultivation, or occasionally to longer distances [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, warming and hyposalinity caused by changes in climate will promote the emergence, growth, and distribution of pathogenic microorganisms (e.g., viruses, bacteria, protozoans) and toxic microalgae (Zgouridou et al, 2022), therefore negatively impacting the immune and metabolic systems of bivalves (Matozzo and Marin, 2011;Turner et al, 2016), leading to severe mortalities. In fact, Reverter et al (2020) reported that most of the infected marine organisms showed higher mortalities at warmer temperatures.…”
Section: Discussionmentioning
confidence: 99%